2017
DOI: 10.1111/wvn.12245
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Promoting Breast Cancer Screening Among Turkish Women With Global Implications: A Systematic Review

Abstract: Background: Breast cancer is a major health concern and remains the most common malignancy in women worldwide and in Turkey. Mammography, clinical breast examination (CBE), and breast self-examination (BSE) are recommended methods to detect early breast cancer in women. Many strategies have been developed to increase the rates of mammography, CBE, and BSE among Turkish women. Despite the benefits of breast cancer screening, these modalities are still underutilized by the majority of Turkish women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our indings are consistent with other studies published in this area of interest (Kumar et al, 1999;Moss et al, 1999). A couple of these studies were also done using retrospectively retrieved data (Secginli et al, 2017;Soo et al, 2001) whereas one study was done using a study population of malignant cases obtained from a can-cer registry (Wallis et al, 1991). However, the current study was done by retrospectively retrieving patient data from a prospectively entered database.…”
Section: Discussionsupporting
confidence: 87%
“…Our indings are consistent with other studies published in this area of interest (Kumar et al, 1999;Moss et al, 1999). A couple of these studies were also done using retrospectively retrieved data (Secginli et al, 2017;Soo et al, 2001) whereas one study was done using a study population of malignant cases obtained from a can-cer registry (Wallis et al, 1991). However, the current study was done by retrospectively retrieving patient data from a prospectively entered database.…”
Section: Discussionsupporting
confidence: 87%
“…Eight reviews 69,[76][77][78]84,89,97,98 included group education, of which one systematic review 69 presented results for breast, cervical and colorectal cancer separately (n = 10).…”
Section: Mass Campaign: Group Educationmentioning
confidence: 99%
“…Breast cancer Five studies 69,76,78,97,98 focused on breast cancer and mixed findings were found for the effectiveness of group education. Both meta-analyses, 76,78 rated as having a low risk of bias and high risk of bias, respectively, reported modest effect at best.…”
Section: Mass Campaign: Group Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not clear which of these initiatives is strategically effective, the need for further education is clear. [18] Although randomized controlled trials have reported that BSE is not effective in early diagnosis in recent years, many organizations indicate that BSE is an important screening method for increasing women's awareness. [19] According to the "National Standards for Breast Cancer Screening Program" in Turkey, while the main screening method is for women aged 40-69 years to have a mammogram every two years, it is recommended that women participating in screening also perform CBE in order to increase the effectiveness of mammography.…”
Section: Introductionmentioning
confidence: 99%